Growth and characterisation of sustainable transparent conducting oxides - Callaghan, Peter (Trinity College Dublin. School of Physics. Discipline of Physics, 2025)
In this thesis the growth and optoelectronic properties of the ternary n-type amorphous zinc tin oxide (a-ZTO) and p-type crystalline V2O3 are discussed in the context of providing suitable and sustainable candidates for transparent conducting oxide applications. As an amorphous ternary oxide the defect chemistry that controls the optical and electronic properties of a-ZTO is complex. While studies have investigated how the Zn/Sn cation ratio affects the charge carrier concentration and mobil- ity, however how these key properties vary in the low thickness regime is not fully understood. a-ZTO thin films were grown by non-reactive magnetron sput- tering, then using a combination of UV-vis spectrophotometry and Hall effect measurements the optoelectronic properties of these films were probed as the thickness was varied. Below 10 nm, the electrical performance is seen to degrade due to reductions in both charge carrier concentration and mobility. In this same range, the optical band gap is observed to rise 0.33 eV. Using X-ray diffraction (XRD) and an in-vacuo sample transfer from magnetron growth chamber to X-ray photoelectron spectroscopy (XPS) the structural and chemical environments of the films were investigated and found to be consistent across the thickness range. Finally, this in-vacuo sample transfer method was employed again to transfer to Scanning Tunneling Microscopy/ Scanning Tunneling Spectroscopy (STM/STS) systems to probe the surface topology and the electronic band gap of the films. STS measurements observe a similar shift in the electronic band gap of the material, confirming the presence and scale of the shift. Next, the local bonding structure in amorphous zinc tin oxide (a-ZTO) is probed to gain insight into charge carrier generation and electron mobility in the material. As an amorphous ternary oxide that acts as an intrinsic semi- conductor, the defect chemistry in the material is quite complex but extremely pertinent to its performance. Using a combination of X-ray Absorption Spectroscopy (XAS) techniques at the Zn and Sn K-edges, I examine the effect varying the inter-cation ratio has on the local chemical and bonding environment of a-ZTO prepared via two growth methods; spray pyrolysis and magnetron sputtering. It is seen that a-ZTO grown by magnetron sputtering shows no changes in the chemical environment as the cation ratio is varied, meanwhile XANES analysis of spray pyrolysis grown samples shows alterations to spectra likely due to the effects caused by different precursors. Although a slight shift in Sn-O bond length is visible between magnetron sputtered and spray grown samples no correlation could be discerned between bond length and variation in cation ratio. It is concluded that a-ZTO, while amorphous over longer ranges, is locally comprised of ZnO and SnO2 ”building blocks”. An alteration in the cation ratio changes the hybridisation at the conduction band minimum resulting in the observed variation in the mobility, charge carrier concentration and band gap. Finally, I performed a study into the growth and optimisation of V2O3 as a candidate p-type TCO. Initial work focused on the growth of high quality, epitaxial V2O3 films on (0001) Al2O3 substrates by reactive magnetron sputtering. High performance p-type behaviour was observed, with a Figure of Merit (FOMG)=455.3±45.5 Ω−1 observed. Following this the effectiveness of Mg as a dopant in the V2O3 films was examined. XPS spectra confirmed the Mg presence in the films, and X-ray Diffraction (XRD) spectra showed the Mg2+ cations did not affect the crystallinity of the V2O3 lattice. However, Mg inclusion was found to have no clear impact on the optical or electrical properties of the V2O3 films. To investigate the Mg incorporation in the V2O3 films a high resolution scanning transmission electron microscopy (STEM) study was performed. This indicated the growth of both corundum and bixbyite phases in both doped and pure V2O3 films. Moreover the bixbyite phases was observed to grow directly on the corundum (0001) Al2O3 substrate. Through energy dispersive X-ray spectroscopy (EDX) mapping the Mg content was observed to be homogeneous amongst the V2O3 films indicating that clustering of MgO along grain boundaries did not occur. Finally, the growth of epitaxial Cu2O thin films was investigated as suitable material to pair with V2O3 in order to form bilayers and nanolaminates with the goal of increasing the p-type conductivity of the composite material. Using XPS the chemical and oxidation state of the films was confirmed while XRD measurements exhibited that epitaxial Cu2O [111] was grown on (0001) Al2O3 substrates. UV-vis spectroscopy measurements indicated an optical band gap of 2.2 eV, in agreement with the expected value from literature.
APPROVED
Keywords: zinc tin oxide; magnetron sputtering; spray pyrolysis; amorphous oxide semiconductor; XANES; EXAFS; X-ray absorption spectroscopy; n-type TCO; p-type TCO; vanadium sesquioxide; transparent conducting oxide; nanolaminates